1999
DOI: 10.1046/j.1570-7458.1999.00537.x
|View full text |Cite
|
Sign up to set email alerts
|

The biology of Penthaleus species in southeastern Australia

Abstract: Earth mites are major pests of pastures and crops within southern Australia. While the biology and ecology of the redlegged earth mite (Halotydeus destructor) have been studied extensively, the blue oat mite (Penthaleus major) and its recently discovered relative, Penthaleus falcatus, have received little attention. The distribution of H. destructor, P. major and P. falcatus is described in Victoria, Australia, and the inland borders in central New South Wales are re-described. A new undescribed Penthaleus spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
66
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(70 citation statements)
references
References 12 publications
4
66
0
Order By: Relevance
“…The signiÞcant increase of H. destructor at all sites at the end of the season is likely to offset the high mortality that occurs during diapause (Ridsdill-Smith 1991, Ridsdill-Smith andAnnells 1997). However, the inability of P. major to increase in abundance when they also have a high reproductive potential (Weeks and Hoffmann 1999) suggests that H. destructor may have had a negative effect on P. major in the Þeld because of limited resources. Experiments conducted herein conÞrm competitive interactions between these species and also indicate that P. major can have a negative impact on H. destructor.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The signiÞcant increase of H. destructor at all sites at the end of the season is likely to offset the high mortality that occurs during diapause (Ridsdill-Smith 1991, Ridsdill-Smith andAnnells 1997). However, the inability of P. major to increase in abundance when they also have a high reproductive potential (Weeks and Hoffmann 1999) suggests that H. destructor may have had a negative effect on P. major in the Þeld because of limited resources. Experiments conducted herein conÞrm competitive interactions between these species and also indicate that P. major can have a negative impact on H. destructor.…”
Section: Discussionmentioning
confidence: 96%
“…However, this is not the case because both P. sp. x and P. falcatus use different hosts to P. major (Weeks and Hoffmann 1999). It is not known if these host differences have arisen from past competition within this complex of earth mite species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have also found differences in the levels of tolerance of mites to pesticides that could be related to control failures. In particular, P. falcatus has a high level of tolerance to a range of registered pesticides compared to other earth mites, and has been responsible for many chemical control failures (Umina & Hoffmann 1999;Weeks & Hoffmann 1999;Robinson & Hoffmann 2000, 2001. Given the high tolerance levels present in Ba.…”
Section: Discussionmentioning
confidence: 99%